The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12325-020-01584-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemopatch® as a Hemostatic Agent is Safe in Partial Nephrectomy: A Large, Single-Surgeon Retrospective Evaluation

Abstract: Introduction Partial nephrectomy (PN) has evolved into the surgical standard of care for localized renal lesions. Hemostatic agents (HA) support the surgeon in achieving local hemostasis during PN. We previously reported initial results with the HA Hemopatch ® in PN. We now report our experiences with Hemopatch ® in a larger and more challenging single-surgeon PN cohort. Methods Our study included 45 patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…HEMOPATCH is a sealing hemostat patch that has been used widely in different surgical elds such as Neurosurgery as dural sealant in cranial and spinal procedures, in pancreatic surgery in order to prevent postoperative pancreatic stula after distal pancreasectomy or in Urology to support the surgeon in achieving local hemostasis during partial nephrectomy or in cardiac surgery [25][26][27][28]. Its application in gynecology has not been evaluated by prospective studies, so we cannot have direct comparisons, except for the use of other topical hemostats, such as Floseal in Ovarian cystectomy, Tisseel and Floseal in laparoscopic myomectomy, and retrospective studies on hysterectomy for pathology benign [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…HEMOPATCH is a sealing hemostat patch that has been used widely in different surgical elds such as Neurosurgery as dural sealant in cranial and spinal procedures, in pancreatic surgery in order to prevent postoperative pancreatic stula after distal pancreasectomy or in Urology to support the surgeon in achieving local hemostasis during partial nephrectomy or in cardiac surgery [25][26][27][28]. Its application in gynecology has not been evaluated by prospective studies, so we cannot have direct comparisons, except for the use of other topical hemostats, such as Floseal in Ovarian cystectomy, Tisseel and Floseal in laparoscopic myomectomy, and retrospective studies on hysterectomy for pathology benign [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are similarities and differences between this series and the previously reported series of PEG-coated patch use in partial nephrectomy. 10 Surgical approach, technique with a hemostatic running suture in the defect base, and RENAL scores were similar. We did not use additional hemostatic agents and did not report any blood transfusion or intervention for bleeding.…”
Section: Cuaj -Techniques In Urologymentioning
confidence: 77%
“…McLarty et al Techniques: PEG-coated patch for MIPN 4 © 2021 Canadian Urological Association 45 patients over a five year period. 10 In this update, they confirmed a PEG-coated patch can be applied to more complex partial nephrectomy patients but reported a 6% rate of intervention for post-operative bleeding.…”
Section: Cuaj -Techniques In Urologymentioning
confidence: 83%
“…Hupe et al reported only a few bleeding events in patients undergoing partial nephrectomy using Hemopatch ® . Most of these procedures were performed as MIS [ 11 ]. Furthermore, Hemopatch® proved to be feasible and reliable in laparoscopic partial nephrectomy [ 7 ] and laparoscopic cholecystectomy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several case series and smaller studies describe the effective and reliable use of Hemopatch ® in a variety of clinical applications, including solid organ, neurological, gastrointestinal, biliopancreatic, endocrine, urologic and cardiovascular procedures [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%